Jatarishun Farm: Alternative Tourism and Kichwa Decolonization Resistance - S. Fortes, Bartira; Wayra Calapi, Miguel (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This study analyzes Tambo Jatarishun as a space for Kichwa decolonial resistance. Through alternative tourism, it articulates proposals for community-based “ecosimía,” health, and autonomous learning that challenge the models imposed by the global system. The work highlights self-management and the reaffirmation of identity as pillars of sustainable development, positioning tourism as a political practice oriented toward territorial sovereignty and cultural revitalization.